Possibilities of feedforward multilayer neural network classifier as a detector of pest birds in vineyards - Doležel Petr; Mariška Martin; Taufer Ivan (Trans Tech Publications, 2015)
In this paper, the application of artificial neural network clasifier to resolve pest birds in agricultural areas as a part of a comprehensive system of protection against vermin is demonstrated. Firstly, the idea of the whole system is outlined. Then, the method of recognition is described, the process of artificial neural network design is illustrated and the classifier is validated using data gathered in the fields. Eventually, the results are compared to similar works.
Možnosti využití dopředné vícevrstvé neuronové sítě jako detektoru škodného ptactva ve vinicích
Keywords: Artificial neural network; signal processing; pest birds; sound recognition; linear predictive coding.